More than just meat: Carcass decomposition shapes trophic identities in a terrestrial vertebrate. (25th March 2022) - Barceló, Gonzalo; Perrig, Paula L.; Dharampal, Prarthana; Donadio, Emiliano; Steffan, Shawn A.; Pauli, Jonathan N.
Abstract: Most food web models fail to account for the full complexity of interactions within a community, particularly where microbes are involved. Carcasses are microbe‐rich resources and may represent a common nexus for the macrobiome and microbiome, effectively uniting autotrophs, consumers, predators and microbiota. We evaluated the role of carcasses as multitrophic resources and explored dietary partitioning for a sexually dimorphic obligate scavenger known for its hierarchical social system. This study was set in a well‐studied community of camelids Vicugna, Lama guanicoe, pumas Puma concolor and Andean condors Vultur gryphus in the Andes. We hypothesized that condors, by feeding on trophically distinct dietary substrates within any given carcass, would have highly variable trophic position (TP) values. Furthermore, we expected that the microbial consumers within the carcass would inflate TP values in both, the carrion and the condors. Thus, we expected that the trophic heterogeneity within a carcass could facilitate sex‐based dietary partitioning in condors. We used a multifaceted approach to assess the foraging of Andean condors, using regurgitated pellet and bulk isotopic analyses, and also quantified the TP of the entire community of graminoids, camelids, camelid carrion, pumas, and female and male condors employing compound‐specific stable isotopes analysis of amino acids. Our analysis of condor pellets and bulk isotopes revealed non‐trivial plant consumption, close to 10% of condor diet. Isotope analysis of amino acids revealed that condors had highly variable TPs (2.9 ± 0.3) compared to pumas (3.0 ± 0.0) and camelids (2.0 ± 0.1), likely representing 'trophic omnivory', wherein the condors consume plants (TP = 1.0 ± 0.1) and microbe‐colonized carrion (2.3 ± 0.1). Female condors exhibited a TP (2.8 ± 0.2) lower than strict carnivory, suggesting that they consume more plant biomass in a carcass, while males (TP = 3.1 ± 0.3) are likely consuming more of the microbe‐rich animal tissue. Our study highlights that carcasses represent a trophically heterogeneous resource and that vertebrate scavengers can feed across trophic groups within the carcass, from autotrophs to secondary consumers, and from both the macrobiome and microbiome. Thus, integration of microbes in macroecological contexts can help to resolve trophic identity, and better characterize the importance of microbes in detritivorous and omnivorous species. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Resumen: La mayoría de los modelos de redes tróficas fallan en capturar la completa complejidad de las interacciones dentro de una comunidad, especialmente cuando hay microbios involucrados. Los cadáveres son un recurso rico en microbios que representa un nexo entre los macro‐ y microbiomas, uniendo efectivamente a autótrofos, consumidores, depredadores y microbios. Evaluamos el rol de los cadáveres como un recurso multitrófico y exploramos la partición dietaria para un carroñero obligado con dimorfismo sexual conocido por su sistema social jerárquico. Este estudio se realizó en una comunidad bien estudiada de camélidos ( Vicugna vicugna, Lama guanicoe ), pumas ( Puma concolor ), y cóndores ( Vultur gryphus ) en los Andes. Hipotetizamos que los cóndores al alimentarse de distintos sustratos tróficos dentro de un cadáver debiesen tener un valor de posición trófica (PT) altamente variable. Además, esperamos que los consumidores microbianos dentro del cadáver aumenten los valores de PT tanto en la carroña como en los cóndores. Por ende, esperamos que la heterogeneidad trófica dentro del cadáver facilite la partición dietaria entre sexos en cóndores. Usamos una aproximación multifacética para evaluar la dieta de los cóndores, usando egagrópilas y análisis de isótopos estables, y también cuantificamos las PT de la comunidad de graminoideas, camélidos, carroña de camélidos, pumas y cóndores macho y hembra empleando análisis de isotopos estables compuesto‐específicos de aminoácidos. Nuestros análisis de egagrópilas e isótopos revelaron consumo no trivial de plantas, cercano al 10% de la dieta del cóndor. Los análisis de isótopos de aminoácidos revelaron que los cóndores tenían una PT altamente variable (2.9 ± 0.3) comparada con pumas (3.0 ± 0.0) y camélidos (2.0 ± 0.1), posiblemente representando "omnivoría trófica", donde los cóndores consumen plantas (TP = 1.0 ± 0.1) y carroña de camélidos colonizada por microbios (2.3 ± 0.1). Cóndores hembra mostraron una PT (2.8 ± 0.2) menor a la carnivoría estricta, sugiriendo que consumen más biomasa vegetal del cadáver, mientras que los machos (TP = 3.1 ± 0.3) están probablemente consumiendo más de los tejidos animales colonizados por microbios. Nuestro estudio destaca que los cadáveres representan un recurso tróficamente heterogéneo, desde autótrofos a consumidores secundarios, y desde el macro y microbioma. Así, la integración de microbios en contextos macroecológicos puede ayudar a resolver las identidades tróficas y caracterizar de mejor manera la importancia de los microbios en especies detritívoras y omnívoras.